Sampaguita Residence Hall a descriptive evaluative study and design synthesis - Dela Rosa, Ferlinda N.
The existing facilities of Sampaguita Residence Hall, a dormitory housing female college students in the University of the Philippines, were described and evaluated to determine if they fulfill the actual needs of the student residents. These were found to be inefficient and inadequate, so a design synthesis is formulated in order to meet the living requirements of the users.